Lifestyle Score and Genetic Factors With Hypertension and Blood Pressure Among Adults in Rural China - Niu, Miaomiao; Zhang, Liying; Wang, Yikang; Tu, Runqi; Liu, Xiaotian; Wang, Chongjian; Bie, Ronghai (Frontiers in Public Health, 2021)
Background: Although high genetic risk and unhealthful lifestyles are associated with a high risk of hypertension the combined relationship between lifestyle score and genetic factors on blood pressure remains limited, especially in resource-constrained areas. Aim: To explore the separate and joint effects between genetic and lifestyle factors on blood pressure and hypertension in rural areas. Methods: In 4592 adults from rural China with a 3-year of follow-up, a genetic risk score (GRS) was established using 13 single nucleotide polymorphisms (SNPs), and the lifestyle score was calculated including diet, body mass index (BMI), smoking status, drinking status, and physical activity. The associations of genetic and lifestyle factors with blood pressure and hypertension were determined with generalized linear and logistic regression models, respectively. Results: The high risk GRS was associated with evaluated blood pressure and hypertension, and the healthful lifestyle was associated with DBP level. Individuals with unhealthful lifestyles in the high GRS risk group, had an OR (95% CI) of 1.904 (1.006, 3.603) for hypertension than those with healthful lifestyle in the low GRS risk group. Besides, the relative risk (RR), attributable risk (AR), and population attributable risk (PAR) for unhealthful lifestyle are 1.39, 5.87%, 0.04%, respectively, and the prevented fraction for the population (PFP) for healthful lifestyle is 9.47%. Conclusion: These results propose a joint effect between genetic and lifestyle factors on blood pressure and hypertension. The findings provide support for adherence to a healthful lifestyle in hypertension precision prevention.